2005
DOI: 10.1161/01.cir.0000165503.08661.e5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effects of Exercise Training in Patients With Chronic Heart Failure

Abstract: Background-In chronic heart failure (CHF), cross-talk between inflammatory activation and oxidative stress has been anticipated in skeletal muscle (SM). The role of the radical scavenger enzymes superoxide dismutase (SOD), catalase (Cat), and glutathione peroxidase (GPX), which remove oxygen radicals, has never been assessed in the SM in this context. Moreover, it remains unknown whether exercise training augments the activity of these enzymes in CHF. Methods and Results-Twenty-three patients with CHF were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
241
2
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(274 citation statements)
references
References 37 publications
12
241
2
19
Order By: Relevance
“…Similar results have been reported regarding the effect of regular exercise training, for example 12 weeks of moderate intensity aerobic exercise performed 3 days a week on antioxidant defence mechanisms resulted in an up-regulation in antioxidant enzymes, evident by an increase in the activity of superoxide dismutase, GPx and catalase [19].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been reported regarding the effect of regular exercise training, for example 12 weeks of moderate intensity aerobic exercise performed 3 days a week on antioxidant defence mechanisms resulted in an up-regulation in antioxidant enzymes, evident by an increase in the activity of superoxide dismutase, GPx and catalase [19].…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that ET in CR improved NO production by increasing phosphorylation of endothelial NO synthase 22) and suppressed oxidative stress by increasing radical scavenger enzyme activity. 23) Taken together, the results suggest that supervised ET protects glomerular endothelial cells by improvement in the balance between NO bioavailability and oxidative stress, leading to a decrease in urinary albumin excretion. eGFR: In the current study, eGFR remained unchanged in the supervised group, whereas it deteriorated in the non-supervised group.…”
Section: Discussionmentioning
confidence: 82%
“…Axel Linke et al 47 Avaliação da atividade enzimática da Catalase, Superóxido Dismutase e Glutationa Peroxidase no músculo esquelético através de biópsia.…”
Section: Autorunclassified